2023
DOI: 10.1038/s41526-023-00250-x
|View full text |Cite
|
Sign up to set email alerts
|

Time perception in astronauts on board the International Space Station

Abstract: We perceive the environment through an elaborate mental representation based on a constant integration of sensory inputs, knowledge, and expectations. Previous studies of astronauts on board the International Space Station have shown that the mental representation of space, such as the perception of object size, distance, and depth, is altered in orbit. Because the mental representations of space and time have some overlap in neural networks, we hypothesized that perception of time would also be affected by sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 46 publications
1
7
0
Order By: Relevance
“…During the test, subjects wore a head-mounted display (Oculus Rift, Oculus VR, Menlo Park, CA), external noisecancelling earphones, and used a finger trackball connected to a laptop to report their responses (Navarro Morales et al, 2023). On the ground, this test was performed in the seated upright position; on the ISS, astronauts were in the free-floating conditions.…”
Section: Experimental Protocolmentioning
confidence: 99%
See 1 more Smart Citation
“…During the test, subjects wore a head-mounted display (Oculus Rift, Oculus VR, Menlo Park, CA), external noisecancelling earphones, and used a finger trackball connected to a laptop to report their responses (Navarro Morales et al, 2023). On the ground, this test was performed in the seated upright position; on the ISS, astronauts were in the free-floating conditions.…”
Section: Experimental Protocolmentioning
confidence: 99%
“…When astronauts were asked to perform periodic arms movements with the same rhythm as a metronome and continue after the metronome had been switched off, the variability of inter-response intervals significantly increased during spaceflight (Semjen et al, 1998a;1998b). During time production tasks, some astronauts overestimated a 2-s interval during a short-duration space flight (Ratino et al, 1988), whereas other astronauts underproduced a 1min interval, and underestimated intervals in the range of hours during long-duration spaceflight compared to preflight baseline (Navarro Morales et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Table 2 shows the number of subjects in each group who performed each test. The astronauts performed the tests ~3 months before launch (Astro Pre), monthly during the spaceflight (duration judgment and reaction time test only) ( 12 , 19 ), and ~2 h after they returned to Earth (R + 0) and 24 h later (R + 1). Tests were performed on R + 0 and R + 1 because previous studies have shown significant changes in spatial orientation, eye movements, postural control, and gait during this period compared to preflight ( 23 ).…”
Section: Methodsmentioning
confidence: 99%
“…Only the “go” and “stop” buttons were displayed during the test. Subjects were not allowed to count the seconds passing by Navarro Morales et al ( 12 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation